2004
DOI: 10.1093/nar/gkh795
|View full text |Cite
|
Sign up to set email alerts
|

A third lineage with two-piece tmRNA

Abstract: tmRNA combines tRNA and mRNA properties and helps bacteria to cope with stalled ribosomes. Its termini normally pair in the tRNA domain, closing the mRNA portion into a looping domain. A striking variation is a two-piece form that effectively breaks open the mRNA domain loop, resulting from independent gene permutation events in alphaproteobacteria and cyanobacteria. Convergent evolution to a similar form in separate bacterial lineages suggests that loop-opening benefits tmRNA function. This argument is streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…We demonstrated unambiguously that pk1 is not an essential component of tmRNA but plays an important role in stabilizing the structure of tmRNAs with long RNA segments connecting the TLD and MLD. Our findings are consistent with comparative analyses of tmRNA sequences, which revealed that in some tmRNAs pk1 could be replaced with either a single-stranded RNA or a single hairpin (Zwieb et al 1999;Gaudin et al 2002;Gueneau de Novoa and Williams 2004;Sharkady and Williams 2004;Andersen et al 2006).…”
Section: Resume Codon-positioning Segment Is Essential For Tmrna Funcsupporting
confidence: 90%
See 2 more Smart Citations
“…We demonstrated unambiguously that pk1 is not an essential component of tmRNA but plays an important role in stabilizing the structure of tmRNAs with long RNA segments connecting the TLD and MLD. Our findings are consistent with comparative analyses of tmRNA sequences, which revealed that in some tmRNAs pk1 could be replaced with either a single-stranded RNA or a single hairpin (Zwieb et al 1999;Gaudin et al 2002;Gueneau de Novoa and Williams 2004;Sharkady and Williams 2004;Andersen et al 2006).…”
Section: Resume Codon-positioning Segment Is Essential For Tmrna Funcsupporting
confidence: 90%
“…These observations provided unambiguous proof that pk1 was not essential for trans-translation. Our finding is consistent with comparative analyses of tmRNA sequences that identified a number of bacterial tmRNAs, in which pk1 was replaced by a single hairpin Gaudin et al 2002;Sharkady and Williams 2004;Andersen et al 2006). In M. pneumoniae, P. marinus, and G. violaceus, the hairpin contained 5 bp.…”
Section: E Coli Tmrna Does Not Require Pk1 For Its Functionssupporting
confidence: 89%
See 1 more Smart Citation
“…5,6 The MLR is much more plastic than the TLD; diverse lineages have lost some or all PKs, and in some cases even the tag reading frame. In three bacterial groups, the alphaproteobacteria, some betaproteobacteria, and some cyanobacteria, tmRNA occurs as two RNA chains joined by base-pairing [7][8][9] ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Usually tmRNA is a single molecule. At least three isolated clades in alphaproteobacteria [197], cyanobacteria [113,437], and beta-proteobacteria [372] have two-component tmRNAs, while jakobids have lost the mRNA-like region in their mitochondrial tmRNAs [179]. Reduction of the tmRNA structure in endosymbionts seems to be a common phenomenon [137].…”
Section: Other Classes Of Small Ncrnamentioning
confidence: 99%